Zmiany na europejskim rynku świadczenia usług nadawczych i audiowizualnych a ramy finansowania publicznego - Rutkiewicz, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The purpose of this paper is an attempt to answer the question about the main directions of changes on the European broadcasting and audiovisual market of public services and making a review of the most important law regulations concerning the state aid granting. In the introduction the author starts from the discussion about the features and reasons of changes on the public services broadcasting market over the last three decades. Then the author briefly summarizes the role of public service broadcasting and presents the legal context of state financing of public service broadcasters. In the last part the author points at the diversification of public broadcasting services.
Keywords: usługi nadawcze; usługi audiowizualne; finansowanie publiczne